2011
DOI: 10.1186/cc10051
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxemia related to cardiopulmonary bypass is associated with increased risk of infection after cardiac surgery: a prospective observational study

Abstract: IntroductionPrevious studies have documented a high frequency of endotoxemia associated with cardiopulmonary bypass (CPB). Endotoxemia may be responsible for some of the complications associated with cardiac surgery. The purpose of the study was to examine the prevalence of endotoxemia during cardiopulmonary bypass supported aortocoronary bypass grafting surgery (ACB) using a new assay, the Endotoxin Activity Assay (EAA), and explore the association between endotoxemia and post-operative infection.MethodsThe s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 29 publications
(32 reference statements)
3
26
0
Order By: Relevance
“…These findings may be of particular interest since they underline the concept that the variations of EA compared to baseline, more than its value at the beginning of the surgical procedure, could be relevant in describing the role of EA after CPB. In accordance, Klein et al [28] found that the maximum EA over the first 24 h, even though within the normal range, was strongly correlated with an increased risk of postoperative complications. Furthermore, it has been observed that ICU patients with dynamic daily variations in endotoxin levels had a greater degree of total organ dysfunction as measured by the Multi Organ Dysfunction Score [29].…”
Section: Discussionsupporting
confidence: 63%
“…These findings may be of particular interest since they underline the concept that the variations of EA compared to baseline, more than its value at the beginning of the surgical procedure, could be relevant in describing the role of EA after CPB. In accordance, Klein et al [28] found that the maximum EA over the first 24 h, even though within the normal range, was strongly correlated with an increased risk of postoperative complications. Furthermore, it has been observed that ICU patients with dynamic daily variations in endotoxin levels had a greater degree of total organ dysfunction as measured by the Multi Organ Dysfunction Score [29].…”
Section: Discussionsupporting
confidence: 63%
“…Further, cardiac malfunctioning alone might cause damages in the alimentary tract mucosal barrier resulting in bacterial and endotoxins translocation to systemic circulation and sepsis. In accordance to this hypothesis, Klein et al 30 stated that the duration of cardiopulmonary bypass increased the risk of endotoxemia and postsurgical infection. 30 Further, complex congenital cardiac diseases were substantially related with the risk of necrotizing enterocolitis.…”
Section: Discussionmentioning
confidence: 80%
“…In accordance to this hypothesis, Klein et al 30 stated that the duration of cardiopulmonary bypass increased the risk of endotoxemia and postsurgical infection. 30 Further, complex congenital cardiac diseases were substantially related with the risk of necrotizing enterocolitis. Even though the enterocolitis was not directly associated with mortality rate, 20% of patients with this inflammatory reaction would die.…”
Section: Discussionmentioning
confidence: 80%
“…[29] The CPB itself provokes a systemic inflammatory response syndrome (SIRS) due to ischemia-reperfusion injury, endotoxemia, operative trauma, non-pulsatile blood flow, and pre-existing left ventricular dysfunction. Inflammatory mediators, such as endotoxin, IL-1b, IL-6, IL-8, and TNF-a, considerably rise during CPB [30] owing to activation of neutrophils and vascular endothelium, elaboration of cytotoxic oxygen-derived free radicals, proteases, cytokines, and chemokines and increased platelet activation, degranulation, and adherence. [31,32] CPB activates factor XII (Hageman factor) to factor XIIa and also results in the activation of intrinsic coagulation system, the kallikrein system, the fibrinolytic system and complement cascade.…”
Section: Aki-cs Incidence Based On Aki Definitionmentioning
confidence: 99%